Mastering a New Language as a Process of Social Adaptation: A Case Study of Transfer Students in Language Learning - David Bastiansyah; Sonny Elfiyanto (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study investigates the challenges faced by transfer students in acquiring a new language and explores the impact of social adaptation on their linguistic proficiency. Utilizing a qualitative case study approach, data were collected through semi-structured interviews and participatory observations. The findings reveal that transfer students struggle with understanding vocabulary, sentence structures, and cultural differences that affect their communication skills. Strategies such as seeking support from peers and teachers and utilizing digital learning tools were found to help students overcome these challenges. Moreover, students who received social support from their peers and educators were more successful in acquiring proficiency in the new language. In contrast, students who experienced social isolation faced more difficulties in language learning. This study highlights the importance of social support in facilitating language acquisition and adaptation for transfer students.